A Study of Psychological Impact of Diagnosis of HIV in Children and Adolescents in Indian Population - Rakesh Gupta; Capt. Sandipan Shringi; Vasudha Mahajan; Venkatesh G; Kalpana Srivastava (HIV/AIDS Research and Treatment-Open Journal, 2015)
Objectives: To identify psychosocial impact in children and adolescents infected with HIV with a view to improve counselling and minimize impact of HIV and improve their quality of life. Material and Methods: This was a cross-sectional study, conducted at a tertiary care hospital among 100 consecutively enrolled HIV infected children between 10 and 18 years of age. A detailed interview on a pretested questionnaire was conducted, which include child’s personal history, knowledge of HIV, psychological concern, behavioral problems on an observation scale. Misconceptions and ignorance about the HIV/AIDS were clarified to the respondents, using this session as an educational tool also. Result: Mean age of study population was 13.8 years with male: female ratio of 0.8:1. Only 65% respondents knew about their HIV status and only 14% had knowledge about mode of spread and prevention. 33 children complained of frequent sicknesses, 23 had feeling of anger, 19 isolation tendencies, 15 were fearful, 12 lost their confidence and 14 children were unable to concentrate on study. 29 children had a feeling of stigma towards HIV, 10 felt discriminated by classmates and community. History of sexual exploitation was given by 6 and bedwetting by 3 children. Thirteen children looked unhappy, 5 felt guilty, 3 were nervous and 1 stared blankly. Majority of respondents (91%) wanted to be a grown up and fight the disease bravely. Conclusion: 65% respondents knew about their HIV status and 14% had knowledge about HIV. The disclosure of HIV was told to only 65% adolescents and most of them by the doctors. There was a significant psychological impact in form of anger, isolation tendencies, fearfulness, loss of confidence, and suicidal tendencies. We need to provide appropriate counseling, education and creative ways to decrease the psychological impact of HIV/AIDS with a view to improve their quality of life.